Reimagining Medusa: The Retranslation of the Monstrous Myth in English Literary Tradition - Mehrpooya, Abbas; Nowroozzadeh, Negar; Bigdeli, Ramtin (LANGUAGE ART, 2026)
This study examines the transformation of Medusa, the infamous Gorgon of Greek mythology, from her earliest classical representations to her multifaceted reinventions in English literary tradition. Tracing her evolution across antiquity, the medieval moral imagination, Renaissance humanism, Romantic aestheticism, and modern feminist reinterpretations, the research explores how Medusa’s image embodies shifting conceptions of power, gender, and identity. Through a comparative textual method grounded in myth criticism, psychoanalytic theory, and feminist approaches, the article reveals how the myth’s enduring adaptability mirrors collective anxieties and cultural self‑reflection. In classical contexts, Medusa symbolizes divine vengeance and the terror of female alterity. By the Renaissance and Romantic eras, writers like Edmund Spenser and Percy Bysshe Shelley transform her into a mirror of human introspection and tragic beauty. Modern authors such as Sylvia Plath, Carol Ann Duffy, and Natalie Haynes reclaim her voice entirely, reconstructing the Gorgon as an emblem of resistance, trauma, and feminist reawakening. The analysis identifies the motif of the ‘gaze’ as the unifying thread across centuries, transmuting from fatal weapon to metaphorical vision of self‑awareness and empowerment. Ultimately, this study argues that Medusa’s continuing resonances demonstrate the dynamism of myth in literary imagination. Her story invites confrontation with the complexities of gender, identity, and monstrosity that persist within Anglophone cum Western culture.